Satisfaction with Appearance and the Desired Treatment to Improve Aesthetics - Bader K. Al-Zarea (International Journal of Dentistry)
Objective. To identify participants’ satisfaction with appearance and the desired treatment to improve aesthetics. Materials and Methods. 220 participants (127 males and 93 females, mean age = 21.4 ± 1.5 years) were recruited into the study. A structured questionnaire was used to assess patients’ satisfaction with appearance and what treatment they desire to improve aesthetics. Participants scored the level of satisfaction with appearance using visual analogue scale. Results. The VAS mean score of satisfaction with general appearance was 6.8 ± 2.3. Half participants were dissatisfied with tooth appearance and 65.9% were dissatisfied with tooth colour. Higher VAS scores were associated with higher desire for all treatments that improve tooth appearance (). Dissatisfaction with tooth appearance increased with increased dissatisfaction with teeth colour, feeling of poor tooth alignment, presence of fractured anterior teeth, and increased desire for orthodontic, crowns, and dentures treatments (). Dissatisfaction with tooth colour was associated with increased desire for tooth whitening and tooth coloured fillings (). Conclusions. Participants had high levels of dissatisfaction with tooth appearance and tooth colour. Dissatisfaction with tooth colour contributed to the increased dissatisfaction with tooth appearance. Dissatisfaction with tooth appearance, colour, alignment, and condition was significantly related to high desire for aesthetic treatments.